The Effect of Chlorhexidine Gluconate Mouthwash in Comparing OHI-S Scores in Students of the Karya Adi Husada Mataram Dental Health Academy - Kurniawati, Heny (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The overall health of the body includes oral and dental health. The aftereffects of the 2018 Riskesdas show that most of the Indonesian populace (94.7%) has great tooth brushing propensities, specifically they have carried out the way of behaving of cleaning their teeth consistently. Sadly, however, only 2.8% of this number brush their teeth correctly, at least twice per day—in the morning after breakfast and at night before bed. The use of chlorhexidine as a mouthwash is a periodontal treatment because it has antiseptic properties, inhibiting plaque formation. The aim of this study was to determine the difference between gargling using Chlorhexidine Gluconate after brushing your teeth and not rinsing your mouth. The research process was carried out at the Karya Adi Husada Mataram Dental Health Academy and was carried out by observing samples between those who gargled using Chlorhexidine gluconate and those who did not gargle. The research results show significant results in the univariate analysis statistical test, namely from the results of statistical tests using the univariate analysis test, the count is 85,154 tables with α0.05, which is 14,6114, meaning the count is greater than the table so Ho is rejected. So it can be concluded that there is a difference in OHIS values ​​between those who gargle Chlorhexidine gluconate and those who do not gargle Chlorhexidine gluconate, where the OHIS value of Chlorhexidine gluconate mouthwash users is better than the OHIS value of students who do not gargle Chlorhexidine gluconate.